2011
DOI: 10.1155/2011/140194
|View full text |Cite
|
Sign up to set email alerts
|

The Strategy of Combining Antidepressants in the Treatment of Major Depression: Clinical Experience in Spanish Outpatients

Abstract: Introduction. The combination of antidepressants is a useful tool in the treatment of major depression, especially in cases where there is a partial response to antidepressant monotherapy. However, the use of this strategy is a matter of controversy, and its frequency of use in clinical practice is not clear. The aim of our study is to assess the use of antidepressants combination in Spain by reviewing three databases used between 1997 and 2001. Methods. Databases pertain to patients who are study subjects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 36 publications
(46 reference statements)
0
10
0
5
Order By: Relevance
“…However, lithium is known to have a narrow therapeutic window and needs blood level monitoring to avoid the toxicity and fatalities associated with high lithium levels 77,78,80. With regard to newer generations of antidepressants, after failure of a first-line SSRI, neither a switch within a class nor a switch to a different class of antidepressant is unequivocally supported by the data, although switching from an SSRI to venlafaxine or mirtazapine may potentially offer greater benefits 7577,141. In an open-label study, mirtazapine was effective in 38% of patients with depression resistant to standard antidepressants.…”
Section: Discussionmentioning
confidence: 98%
“…However, lithium is known to have a narrow therapeutic window and needs blood level monitoring to avoid the toxicity and fatalities associated with high lithium levels 77,78,80. With regard to newer generations of antidepressants, after failure of a first-line SSRI, neither a switch within a class nor a switch to a different class of antidepressant is unequivocally supported by the data, although switching from an SSRI to venlafaxine or mirtazapine may potentially offer greater benefits 7577,141. In an open-label study, mirtazapine was effective in 38% of patients with depression resistant to standard antidepressants.…”
Section: Discussionmentioning
confidence: 98%
“…Other combinations, such as monoamine oxidase inhibitors (MAOI) + tricyclic antidepressants (TCA) or SSRIs + TCA, have less support but were also formerly widely used and accepted in clinical practice [19, 22]. More controversial, the combination of more than two antidepressants is less well studied and reported [1315, 22]. This may be associated with the possibility of a greater side-effect burden (including serotoninergic syndrome and syndrome of inappropriate antidiuretic hormone secretion, SIADH) and with higher clinically significant medication interactions secondary to polypharmacy [14].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this latter strategy, although combining two antidepressants with complementary pharmacological actions is well accepted, the triple antidepressant combination is, on the contrary, less described and more controversial [1316]. Here, we present a relapse of moderate-to-severe depressive symptoms in a patient with treatment-resistant depression that was efficaciously treated after adding trazodone to a dual antidepressant combination consisting of paroxetine and mirtazapine (in standard doses); we also discuss the pros and cons of combining three antidepressants as a strategy in the management of treatment-resistant depression.…”
Section: Introductionmentioning
confidence: 99%
“…A study of 12 European countries, including the UK, found the prevalence of adjunctive antidepressant therapy to be less than 7% [16]. Similarly, a study in Spain found the prevalence of adjunctive antidepressant therapy to be 8.3% among patients treated for MDD [17]; several other studies have reported a range of adjunctive therapy prevalence of between 2% to 25% [16,18,19]. Reflecting a different health care system, a study based on a US insurance claims database found that 38% of patients who initiated on SSRI monotherapy received adjunctive treatment in the year following the initial index prescription [20].…”
Section: Discussionmentioning
confidence: 99%